To investigate whether VEGF and KDR polymorphisms are associated with chronic Achilles tendinopathy and self-reported measurements of tendon pain - Brazier, Christina Daniela (Department of Human Biology, 2025)
Background: Chronic Achilles tendinopathy (AT) is prevalent in the sporting population, specifically in sporting codes with a large running component, and presents as swelling, impaired lower limb function, and pain of insidious onset. Although the mechanisms are unclear, current theories implicate structural changes and neovascularisation in tendinopathy. Vascular endothelial growth factor (VEGF) and its receptor referred to as kinase domain receptor (KDR) are key regulators of neovascularisation and can be associated with pain. Common DNA sequence variants within the VEGFA and KDR genes have previously been associated with musculoskeletal soft tissue injuries, including AT. The primary aim of this dissertation was to identify whether VEGF and KDR variants were associated with (i) the severity of AT, (ii) AT ultrasound findings and (iii) self-reported measurements of Achilles tendon pain using multidimensional pain scales. Methods: One hundred and eighty-five recreational athletes with clinically confirmed Achilles tendinopathy for at least 3 months were recruited from Cape Town, South Africa. The injured and uninjured Achilles tendons were examined using conventional grayscale ultrasound. Tendinopathy pain was rated by completing the Victorian Institute Sports Assessment - Achilles (VISA-A), Short-form McGill Pain Questionnaire (sf- MPQ), and Short-form Brief Pain Inventory (sf-BPI) questionnaires. One hundred and ninety-four asymptomatic healthy appropriately matched individuals with no history of tendon injuries were also recruited for this study. Participants were genotyped for VEGFA rs699947 (C/A), VEGFA rs2010963 (G/A), KDR rs2071559 (G/C) and KDR rs1870377 (T/A). Results: Although the VEGFA and KDR variants were not associated with AT, either independently, as inferred haplotypes or via allele interactions, (i) the VEGFA rs699947 CC genotype was significantly associated with decreased risk of bilateral AT, (ii) the A-G VEGFA inferred haplotype constructed from rs699947 and rs2010963 was associated with increased risk of bilateral AT, (iii) the KDR rs2071559 AA genotype was significantly associated with increased risk of a history of multiple (two or more) AT, (iv) the G-T and A-A KDR inferred haplotypes constructed from rs2071559 and rs1870377 were associated with decreased risk and increased risk of multiple and/or bilateral AT, respectively, and (v) the C-G and A-A VEGFA rs699947 and KDR rs2071559 allele-allele interactions were significantly associated with decreased and increased risk of bilateral or multiple injuries respectively. There were no significant differences in the diameters or the relative number of abnormal ultrasound findings of the injured and uninjured Achilles tendons between the VEGFA and KDR genotype groups. Finally, there were no significant differences in VISA-A, sf-MPQ and sf-BPI scores, as well the subscale scores between the VEGFA and KDR genotype groups. Conclusion: The novel findings of this dissertation implicate the VEGF and KDR genes, and by implication the potential biological role of the angiogenesis signalling pathway, with bilateral and/or multiple Achilles tendinopathy risk. The investigated variants within these genes however were not associated with tendon diameters, the relative number of abnormal ultrasound findings or self-reported Achilles tendon pain measured using multidimensional pain scales.